2015
DOI: 10.1007/s12035-015-9544-0
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Resolving Lipid Mediators Improve Neuronal Survival and Increase Aβ42 Phagocytosis

Abstract: Inflammation in the brain is a prominent feature in Alzheimer’s disease (AD). Recent studies suggest that chronic inflammation can be a consequence of failure to resolve the inflammation. Resolution of inflammation is mediated by a family of lipid mediators (LMs), and the levels of these specialized pro-resolving mediators (SPMs) are reduced in the hippocampus of those with AD. In the present study we combined analysis of LMs in the entorhinal cortex (ENT) from AD patients with in vitro analysis of their direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
191
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(203 citation statements)
references
References 87 publications
12
191
0
Order By: Relevance
“…70,71 DHA and SPMs are impaired at the periphery and in the brains of AD patients. 72,73 Interestingly, decreased DHA distribution in AD patient brains correlates with synaptic loss rather than amyloid beta (Aβ) deposition. 74 In addition, DHA or SPMs promote phagocytosis of Aβ42 by microglia 75 and modulate microglia number and activation in vivo.…”
Section: Dietary Omega-3 Pufa Regulate Neuroinflammation and Ecbs: Romentioning
confidence: 99%
See 1 more Smart Citation
“…70,71 DHA and SPMs are impaired at the periphery and in the brains of AD patients. 72,73 Interestingly, decreased DHA distribution in AD patient brains correlates with synaptic loss rather than amyloid beta (Aβ) deposition. 74 In addition, DHA or SPMs promote phagocytosis of Aβ42 by microglia 75 and modulate microglia number and activation in vivo.…”
Section: Dietary Omega-3 Pufa Regulate Neuroinflammation and Ecbs: Romentioning
confidence: 99%
“…Thus, blueberry juice significantly improved word list recall and paired associate learning in older men and women with agerelated memory decline that consumed it, relative to baseline, with paired associate learning also significantly improved relative to placebo controls. 97 A recent study 98 that measured similar cognitive tasks as those in the rodent studies, showed that freezedried blueberries (24 g/day, equivalent to one cup of fresh blueberries) for 90 days improved two measures of executive function in older adults (ages [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. Participants in the blueberry group showed significantly fewer repetition errors in the California Verbal Learning test as well as reduced switch cost on a taskswitching test across study visits, relative to controls who consumed placebo powder.…”
Section: Dietary Interventions With Polyphenolic-rich Foods Can Impromentioning
confidence: 99%
“…For example, these tissues, to name a few, include human blood [3, 4], lymph nodes [4], human brain [5], human placenta [6], breast milk [7, 8] and human kidney [2]. The SPM are clearly endogenous mediators that, given their presence in human organs and tissues, may have additional physiologic roles in their tissue of origin in addition to their functions in activating endogenous resolution circuits in inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Increased arginase activity has been associated with alternatively activated microglia/macrophages (M2) (Gensel and Zhang 2015, Ransohoff and improve neuronal survival and Aβ 2 phagocitosys in vitro (Zhu et al 2016). …”
Section: Discussionmentioning
confidence: 99%